2003
DOI: 10.1007/s00415-003-0258-2
|View full text |Cite
|
Sign up to set email alerts
|

The cerebellum and cognition

Abstract: The aim of this study was to assess cognitive function in patients with spinocerebellar ataxia type 6 (SCA6), an autosomal-dominantly inherited disease leading to a progressive cerebellar syndrome. In contrast to other SCA types, the pathological changes are mostly restricted to the cerebellum. Cognitive function was studied in 12 patients with genetically confirmed SCA6 (mean duration of disease: 9.2 +/- 11.6 years) and 12 age- and IQ-matched controls using a test battery comprising tests for IQ, attention, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…Because lesions in SCA6 patients are restricted to the cerebellum, we suggest that the cognitive dysfunction in SCA6 patients derives from the disruption of the cortico-cerebellar loop. There are a few studies that address cognitive function in SCA6 patients, and a previous study could not disclose a significant impairment of attention, working memory, verbal and visuospatial memory, or fronto-executive functions [11]. However, the lack of statistical significance in their study may be due to an insufficient sample size of SCA6 patients or to other methodological issues such as different neuropsychological tests.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Because lesions in SCA6 patients are restricted to the cerebellum, we suggest that the cognitive dysfunction in SCA6 patients derives from the disruption of the cortico-cerebellar loop. There are a few studies that address cognitive function in SCA6 patients, and a previous study could not disclose a significant impairment of attention, working memory, verbal and visuospatial memory, or fronto-executive functions [11]. However, the lack of statistical significance in their study may be due to an insufficient sample size of SCA6 patients or to other methodological issues such as different neuropsychological tests.…”
Section: Discussionmentioning
confidence: 96%
“…So far, however, only a few studies have examined the rCBF of SCA6 patients [10]. Globas et al failed to provide clear evidence for cognitive deficits in SCA6 patients [11]. However, we recently revealed significant impaired visual memory and verbal fluency in genetically confirmed SCA6 patients [12], suggesting that SCA6 patients have prefrontal dysfunction.…”
Section: Introductionmentioning
confidence: 94%
“…There have been very few studies addressing cognitive function in SCA6 patients because researchers assume, and it is indeed true, that SCA6 patients are rarely impaired in cognitive function (0–20%) [18,47,48,49]. Globas et al [50] examined cognitive function in 12 patients with genetically confirmed SCA6, but found only mild deficits in fronto-executive tasks that were not significantly different from those in controls. However, Suenaga et al [51] examined cognitive function in 18 patients with genetically confirmed SCA 6, and showed that verbal fluency and immediate visual memory were markedly impaired.…”
Section: Spinocerebellar Ataxia Typementioning
confidence: 99%
“…Therefore, patients with SCA6 are an excellent model to reveal the contribution of the cerebellum to cognition. However, only a few studies have reported cognitive impairment in patients with SCA67 and thus cognitive dysfunction in SCA6 patients has not been well elucidated. Furthermore, the mechanism of cerebellar involvement in cognitive dysfunction in patients with SCA6 has not been described.…”
mentioning
confidence: 99%